2018
DOI: 10.17146/aij.2018.593
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Population and Aflatoxin Contamination on Stored Gamma-Irradiated Nutmeg (Myristica fragrans) Kernels

Abstract: A study on the effectiveness of gamma irradiation at doses of 5 and 10 kGy on fungal population, Aspergillus flavus strains, and aflatoxin B1 contamination on stored nutmeg kernels was conducted. The kernels were collected from seeds in a period of one week from the ground at North Sulawesi Province, Indonesia. Dried shelled kernels with ± 10 % moisture content, packed in polyethylene bags at 2.1 kg/bag, were irradiated at 5 and 10 kGy and stored at ambient temperature (28 °C) for 2 and 4 months. Kernel moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Al-Bachir (2016) stated that microbial load in irradiated peanuts significantly decreased when applied with gamma irradiation, resulting in enhanced safety of the product. Nurtjahja et al (2018) reported that irradiated nutmeg at 5-10 kGy reduced the fungal population and no aflatoxin B1 that could be stored up to 4 months at ambient temperature (28 °C). Moreover, thermal processing methods including boiling may affect the quality of cooked products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Bachir (2016) stated that microbial load in irradiated peanuts significantly decreased when applied with gamma irradiation, resulting in enhanced safety of the product. Nurtjahja et al (2018) reported that irradiated nutmeg at 5-10 kGy reduced the fungal population and no aflatoxin B1 that could be stored up to 4 months at ambient temperature (28 °C). Moreover, thermal processing methods including boiling may affect the quality of cooked products.…”
Section: Introductionmentioning
confidence: 99%
“…Nurtjahja et al . (2018) reported that irradiated nutmeg at 5–10 kGy reduced the fungal population and no aflatoxin B1 that could be stored up to 4 months at ambient temperature (28 °C). Moreover, thermal processing methods including boiling may affect the quality of cooked products.…”
Section: Introductionmentioning
confidence: 99%
“…As for other cases of rejection, they occur due to the lack of health certificate in the product's reason (Badan Karantina Pertanian, 2016). The rejection of Indonesian nutmeg has an impact on the economy which also directly affects the welfare of farmers and is detrimental to the image of Indonesia as the producer of nutmegs with the best quality in the world (Nurtjahja, et al, 2018;Wang & Lee, 2017). The low quality of the nutmeg is caused by several factors including lack of maintenance, low productivity because half of the plants are old or not productive and have not used high-quality seeds, farmer institutions that are still weak, and low production quality.…”
Section: Introductionmentioning
confidence: 99%